REINVENTING KEPEMIMPINAN DI SEKTOR PUBLIK UNTUK MEMBANGUN KEPERCAYAAN WARGA KEPADA PEMERINTAH - Silalahi, Ulber (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
Leader and leadership are two important terminologies in public administration. A leader may use his/her leadership to inspire, motivate, and influence his/her employees to achieve desired goals. The recent condition shows political bureaucracy and administration have been unfavorable in generating such leadership. It is, thus, necessary to re-invent public leadership in order to be able to empower public organizations and society. Reinventing means to change the leaders' attitudes to make people trust the government. Public leaders expected by society are those who are honest, visionary, inspiring, skillful, competent, consistent, loyal, and open. Good leaders are supposed to be sensitive with current issues and put public interest on the first place. Meanwhile, bad leadership leads to poor government performance and deteriorating public trust.